Pengaruh Pendidikan Gizi Melalui Media Buku Saku Dengan Metode Ceramah Terhadap Pengetahuan Gizi Atlet Di Pusat Pendidikan Dan Latihan Pelajar (PPLP) Provinsi Nusa Tenggara Barat Tahun 2018 - Rina Susanti; Reni Sofiyatin; Lalu Abdi; Luh Suranadi (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. Based on the result survey preface in 2015 about athlete’s nutritions intake in central of student’s education and training (PPLP) in West Nusa Tenggara known the average of nutrition’s intake include calorie (62,55%), protein (74,41%) and carbohydrate (53,91%) intake on level medium deficit till serious deficit towards 10 athletes from pencak silat and volleyball. Purpose : To know the effect of nutrition education by using a nutrition pocket book and speech about athlete’s knowledge. Research Methods. In this study used quasi experimental with pre and post test with control group design used was The intervention will be given during 14 days and the evaluation will be one day a week for group with the intervention. An instrument of this study was using questioner with total question about 20 numbers. The results were analyzed by using statistic non parametric with Wilcoxon method with significant level (α=0,05. Research Result. The results were analyzed by using statistic non parametric with Wilcoxon method with significant level (α=0,05).  Conclusion. The result showed that ρ=0,027 (<α=0,05) that indicating there are significant effect of knowledge by using nutrition pocket